An adolescent girl with syndrome of inappropriate antidiuretic hormone secretion preceding the diagnosis of olfactory neuroblastoma – a case report - Sasidharan Pillai, Sabitha; Boxerman, Jerrold L.; Groblewski, Jan C.; DeNardo, Bradley D.; Faizan, Mohammed K.; Topor, Lisa Swartz; Robilliard, Renee; Serrano-Gonzalez, Monica (Frontiers in Endocrinology, 2024)
We present an adolescent in whom olfactory neuroblastoma (ONB) was detected on follow-up magnetic resonance imaging (MRI) 2.5 years after SIADH diagnosis. Our case contrasts prior pediatric reports in which ONB and SIADH were diagnosed concurrently.A previously healthy 13-year-old girl was found to have SIADH during evaluation for restrictive eating. Work-up ruled out adrenal, thyroid and paraneoplastic causes, diuretic use, and vasopressin receptor and aquaporin channel mutations. Brain MRI was normal except for paranasal sinus (PNS) inflammatory changes to the left fronto-maxillary sinuses and frontoethmoidal recess. The sodium levels normalized with fluid restriction (800-900 ml/m 2 /day).Multiple repeated attempts to liberalize fluid intake resulted in recurrent hyponatremia. Follow-up brain MRIs 4 and 11 months after the initial presentation showed persistent PNS inflammatory changes. A subsequent brain MRI 31 months after initial presentation demonstrated a lesion in the left frontoethmoidal recess extending into the left nasal cavity and biopsy showed low grade ONB.The patient underwent surgery with normalization of serum sodium on liberalized fluid intake.Seven days after surgery, she had recurrence of SIADH, and brain MRI showed remnant of the ONB at the fovea ethmoidalis. She completed adjuvant radiotherapy though her SIADH persisted.Our case highlights the importance of considering ONB in the evaluation of children with SIADH. Idiopathic SIADH is rare in children and if no cause is identified, computed tomography of sinuses and nasal endoscopy should be considered earlier in the work-up of these patients, particularly in the absence of the sinus symptoms.